ANALYZING THE TREND OF LOGO DESIGN OF NORTH SULAWESI LOCAL CULINARY STARTUPS - Rampen, Dio B.; Tulung, Joy E.; Wangke, Shinta J.C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Marketing and advertising trends, go in and out of style with the seasons and the years. In decades past, advertisements were once created entirely out of text. But as cameras got better, printers more detailed, and digital marketing came to the forefront, advertising shifted to a visual medium. In a general overview of the top companies in the U.S., there seems to have been a shift towards more simplistic even minimalist design practices. In trying to objectively measure a design, there are many factors to consider if one wishes to categorize simple versus complex. Through the use of a visual content analysis, this study explored the evolution of 20 of the top U.S. companiesâ€™ logos over the course of four different design iterations. In comparing logo design trends over time, this study examined simplicity as a function of several different design variables, as well as textual elements used with these company logos. Due to the exploratory nature of this study, portions of this particular study were unable to assert with statistical relevance that visual design variables were a factor in this simplification. However, it was discovered that textual elements, as a portion of the logo, were changing in terms of the number of characters used within the design. Although this study was unable to support several of the initial assumptions the researcher held, it does provide a valuable framework for further research.Â Keyword: trend, startup, logo, design